Toxic Effects Associated With Neonicotinoid Exposure on Non-target Organisms: A Review - Khurana, Leena; Chaturvedi, Payal; Sharma, Charu; Bhatnagar, Pradeep; Gupta, Nidhi (Toxicology International, 2023)
The neonicotinoid class of insecticide is nicotine-like neuro-toxicants used to control the pests of agriculture crops and ornamental plants. They act as selective agonists of acetylcholine receptors in the central nervous system of insect pests and work by disrupting their nerve impulses. Some of the properties of this class of insecticides are a long half-life in soil, low volatility, and higher water solubility, leading to their accumulation in soil, underground water, and water bodies due to surface runoff. This, in turn, results in exposure to many beneficial non-target aquatic and soil fauna such as arthropods, fish, birds, mammals, etc. Although it has a selective mode of action for insects, some in vivo and in vitro investigations have also shown toxicity in non-target invertebrates and vertebrates. Initially, neonicotinoid toxicity was observed in honey bees, which are essential pollinators of crops. Later, studies reported the accumulation of neonicotinoid residues leading to the mortality of aquatic fauna, including salt marsh and freshwater mosquitoes, brine shrimp, fleas, and crayfish. Imidacloprid exposure led to disruption of larval development in the Mayfly larvae. Also, earthworms that play a crucial role in enhancing soil fertility were drastically affected by acetamiprid, clothianidin, imidacloprid, nitenpyram, and thiacloprid. Apart from these, toxicological impacts were also observed in vertebrates such as birds, where imidacloprid, clothianidin, acetamiprid, and thiacloprid caused reproductive, metabolic, and morphological alterations. Similarly, imidacloprid and acetamiprid caused gills, brain and liver dysfunction with embryo mortality. Even after the selective action of neonicotinoids, instances of mammalian toxicity were also reported in many in vivo studies. DNA damage and liver dysfunctions due to imidacloprid in rabbits were observed in various studies. In a recent study, imidacloprid exposure led to DNA damage and oxidative stress in bone marrow-derived mesenchymal cells of buffalo. Also, many instances of neurotoxicity, reproductive toxicity, immunotoxicity, genotoxicity and cytotoxicity in mouse and rat models were observed due to different neonicotinoids. Many in vitro studies using mammalian cell lines have also established potential risks of neonicotinoid exposure. This review, therefore, is a compilation of various toxicity studies of different types of neonicotinoid pesticides in both nontarget invertebrates and vertebrates, including several kinds of toxicities caused in mammals with neonicotinoid exposure.